2017
DOI: 10.1007/s10096-017-2899-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-producing Klebsiella pneumoniae bloodstream infection in critically ill patients: risk factors and predictors of mortality

Abstract: A significant increase in carbapenemase-producing Klebsiella pneumoniae (CP-Kp) bacteraemias has been observed worldwide. The objective of the present work was to study the risk factors and predictors of mortality of CP-Kp bacteraemias among critically ill patients. During a 4-year period (2012-3015), a matched 1:2 case-control study was conducted. Klebsiella pneumoniae was identified by Vitek 2 technology. Antibiotic susceptibility was performed by the agar disc diffusion method and Etest. The presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 16 publications
4
48
2
1
Order By: Relevance
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…The most frequent type of bacteria included were KPC-producing K. pneumoniae, although some studies included mainly OXA-48 producers (212,220,235), NDM producers (219), or noncarbapenemase producers (230). Some studies focused on specific populations, such as intensive care unit (ICU) patients (221,230), hematological or cancer patients (224, 225, 233), or children (219,232). As Tables 4 and 5 show, some studies found combination therapy to be associated with lower mortality rates, while others did not.…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…Carbapenemase-producing Enterobacteriaceae which carry the blaKPC gene (CPE-KPC) stand out among bacteria of epidemiological importance which present unrestrained growth in its resistance profile. These microorganisms spread rapidly and end up being associated with a high mortality rate by limiting the therapeutic options for infected patients (5,(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the rate of mortality in our patients with CRKP BSI was higher (65%) compared to the findings of previously studies [27]. Previous studies have evaluated several risk factors for the mortality associated with CRKP BSI, including use of corticosteroid, use of invasive devices, septic shock and exposure to carbapenems [27][28][29]. Fig-4 shows that CRKP BSI was related to gastrointestinal hemorrhage, Pitt bacteremia score, Charlton comorbidity index and Corticosteroids use and Septic shock.…”
Section: Therapeutic Characteristicsmentioning
confidence: 49%